Environmental ethics and behavioural change - Franks, Benjamin; Hanscomb, Stuart; Johnston, Sean F. (Routledge, an imprint of the Taylor & Francis Group, 2018)
"Environmental Ethics and Behavioural Change takes a practical approach to environmental ethics with a focus on its transformative potential for students, professionals, policy makers, activists, and concerned citizens. Proposed solutions to issues such as climate change, resource depletion and accelerating extinctions have included technological fixes, national and international regulation and social marketing. This volume examines the ethical features of a range of communication strategies and technological, political and economic methods for promoting ecologically responsible practice in the face of these crises. The central concern of the book is environmental behaviour change: inspiring, informing and catalysing reflective change in the reader, and in their ability to influence others. By making clear the forms of environmental ethics that exist, and what each implies in terms of individual and social change, the reader will be better able to formulate, commit to, articulate and promote a coherent position on how to understand and engage with environmental issues. This is an essential companion to environmental ethics and philosophy courses as well as a great resource for professionals interested in practical approaches to environmental ethics. It is also excellent supplementary reading for environmental studies, environmental politics and sustainable consumption courses."--Publisher.